Histopathological changes induced after oral administration of acetamiprid in kidneys of male albino mice - Maha A. Gathwan (Journal of Madenat Alelem University College, 2016)
Repeated oral administration of (10 and 20 mg/ml) of Acetamiprid (ACP) - a neonicotinoid insecticide that is effective against both soil and plant insects (LD50=200mg\kg), for 14 days in male albino mice aged (6-7weeks) induced significa\4nt changes in the histoarchitecture of the kidneys included marked congestion, tubular cell degeneration and sloughing of epithelial cells. haemorrhage and sever necrosis observed depend on the dose . The oral toxicity study of (ACP) revealed that this neonicotinoid insecticide is of highly risk in albino mice.